Improved expansion of human bone marrow‐derived mesenchymal stem cells in microcarrier‐based suspension culture. (11th June 2012) - Yuan, Yifan; Kallos, Michael S.; Hunter, Christopher; Sen, Arindom
Abstract Human bone marrow‐derived mesenchymal stem cells (hBM‐MSCs) have potential clinical utility in the treatment of a multitude of ailments and diseases, due to their relative ease of isolation from patients and their capacity to form many cell types. However, hBM‐MSCs are sparse, and can only be isolated in very small quantities, thereby hindering the development of clinical therapies. The use of microcarrier‐based stirred suspension bioreactors to expand stem cell populations offers an approach to overcome this problem. Starting with standard culture protocols commonly reported in the literature, we have successfully developed new protocols that allow for improved expansion of hBM‐MSCs in stirred suspension bioreactors using CultiSpher‐S microcarriers. Cell attachment was facilitated by using intermittent bioreactor agitation, removing fetal bovine serum, modifying the stirring speed and manipulating the medium pH. By manipulating these parameters, we enhanced the cell attachment efficiency in the first 8 h post‐inoculation from 18% (standard protocol) to 72% (improved protocol). Following microcarrier attachment, agitation rate was found to impact cell growth kinetics, whereas feeding had no significant effect. By serially subculturing hBM‐MSCs using the new suspension bioreactor protocols, we managed to obtain cell fold increases of 103 within 30 days, which was superior to the 200‐fold increase obtained using the standard protocol. The cells were found to retain their defining characteristics after several passages in suspension. This new bioprocess represents a more efficient approach for generating large numbers of hBM‐MSCs in culture, which in turn should facilitate the development of new stem cell‐based therapies. Copyright © 2012 John Wiley & Sons, Ltd.